The Demand to Cassation in the Jordanian Legislation - Al-Alwan, Sarah (Political Sciences and Law Series, 2024)
The demand to cassation is a procedure that aims at referring appellate provisions that are not subject to appeal to the Court of Cassation; some regulations of appellate provisions are directly subject to appeal, while others can only be appealed through permission to cassation. The study aims to understand the nature of permission to cassation, its reasons, and the accuracy of the legislator in regulating this issue. The main problem of the study lies in the lack of precision in the legal texts regulating the issue of demanding permission to cassation procedurally, as well as the legislation suffering from deficiencies and confusion in regulating the issue of reviewing as the most important consequence of the decision issued in response to the demand for cassation in form. The study concluded that the legal texts regulating this issue are deficient and not precise, and that it is necessary to amend the legal texts regulating the demand to cassation , most importantly amending articles (191) and (204) of the Civil Procedure Code to make the procedures and deadlines for demanding cassation clear and specific.‏